YIELD MANAGEMENT IMPLICATION IN ACCOMMODATION BUSINESS (Third Sector Social Economic Review, 2024)
The concept of yield management, which was first introduced for profit maximization in American airlines and continues to develop, matches the supply of a perishable good with the estimated demand through strategies that manipulate the price and consumption time. The aim of this study is to scan the literature of accommodation businesses, which are an important source of economic income in our country despite being heavily exposed to demand fluctuations, on the use of accommodation businesses according to their capacity, stock control, demand forecasts and pricing strategies within the scope of yield management and to reveal the current situation. Within the scope of this research, academic literature on yield management and accommodation businesses is examined and a comprehensive review of the articles published in the existing literature on the focus of the research is presented. This study is important in that it will indicate the knowledge and usage situations regarding yield management in accommodation businesses.
Keywords: Yield management; accommodation businesses; profit maximization; yield management approaches; demand system